Strategi Pendidikan Moderasi Beragama: Peran Guru, Kepala Madrasah, dan Pengawas dalam Era Teknologi - Siti Rodiyah (PT MITRA JURNAL INDONESIA, 2024)
Abstract Religious modernization refers to the life of humanity where religious practices are influenced by political, economic, psychological, scientific, technological, and informational advancements. The current generation, shaped by the Fourth Industrial Revolution, is skeptical and highly dependent on technology while valuing privacy. This generation requires a unique educational approach. The study aims to explore the roles of teachers, school principals, and supervisors in fostering a moderate religious attitude among students through effective educational systems. Using a qualitative approach and literature review as the primary method, the research analyzed data through descriptive analysis. The results highlight the importance of collaborative efforts between educators and institutions to promote inclusive and tolerant religious practices. This includes leveraging technology as a medium to instill moderation values effectively. Abstrak Modernisasi keberagamaan adalah kehidupan umat manusia yang terkait dengan perilaku dalam menjalankan ajaran agamanya yang dipengaruhi oleh perkembangan politik, ekonomi, psikologi, ilmu pengetahuan, teknologi, dan informasi. Generasi masa kini, yang terbentuk oleh Revolusi Industri 4.0, cenderung skeptis dan sangat bergantung pada teknologi serta menjunjung tinggi privasi. Penelitian ini bertujuan untuk mengeksplorasi peran guru, kepala madrasah, dan pengawas dalam menanamkan sikap keberagamaan moderat melalui sistem pendidikan yang efektif. Dengan pendekatan kualitatif dan metode studi pustaka, penelitian ini menganalisis data secara deskriptif. Hasil penelitian menunjukkan pentingnya kolaborasi antara pendidik dan institusi untuk mendorong praktik keberagamaan yang inklusif dan toleran. Pemanfaatan teknologi sebagai media untuk menanamkan nilai-nilai moderasi menjadi salah satu strategi efektif.